Reliability of Circumferential Bone Level Assessment around Single Implants in Healed Ridges and Extraction Sockets Using Cone Beam CT. (18th October 2011) - Raes, Filiep; Renckens, Liesbet; Aps, Johan; Cosyn, Jan; De Bruyn, Hugo
ABSTRACT Purpose: Cone beam computerized tomography (CBCT) provides three‐dimensional information and could absolutely be useful for evaluating circumferential implant bone levels. However, the accuracy and precision of the technique has not been described. The aim of the study was to assess the accuracy and precision of CBCT (i‐CAT®, Imaging Sciences International®, Hatfield, PA, USA) using periapical radiographs (PA) as a reference and to evaluate the circumferential bone level on CBCT around immediately loaded single implants placed in healed ridges (CIT, conventional implant treatment) and extraction sockets (IIT, immediate implant placement). Materials and Methods: PA and CBCT radiographs were obtained from 26 single Astra Tech Osseospeed™ implants (Astra Tech AB, Mölndal, Sweden) 1 year after loading in respectively healed ridges (CIT) or extraction socket (IIT). For accuracy analysis, the three mesial and three distal interproximal levels obtained by CBCT were pooled to enable a comparison with PA. Precision was analyzed by intra‐ and interexaminer reliability calculation from mesial and distal sites on CBCT. The circumferential bone level considered all eight positions assessed on CBCT. Results: Accuracy of CBCT was low (R = 0.325/p = .019) given the fact that bone level of the total group was 0.70 mm (standard deviation [SD] 0.78, range 0.00–3.20) on PA and 0.23 mm (SD 0.27, 0.00–1.20) on CBCT (p < .001) with only 42% of the measurements showing deviation within 0.2 mm. However, intra‐ and interexaminer reliability were favorable (R ≥ 0.611/p < .001, ≥83%). The mean circumferential bone level on CBCT was 0.21 mm (SD 0.30) and 0.26 mm (SD 0.18) for IIT and CIT, respectively. The impact of the treatment strategy was not significant. Conclusion: PA should be the standard technique to assess interproximal bone level but correlates poorly with the CBCT measurements. However, the precision of CBCT was high. CBCT requires further improvements of hardware and/or software. Within the limitations of the study, there is an indication that the buccal bone 1 year after implant treatment is evenly preserved when implants are immediately loaded in extraction sockets or in healed bone.